Selected socio-economic aspects of the integration of Ukrainians: Evidence from the Czech Republic - Linda Danielova; Radka Prokešová; Jitka Vacková; Renata Švestková; Lesia Shuranova (Problems and Perspectives in Management)
The war against Ukraine has led to a substantial influx of Ukrainian migrants into many countries, including the Czech Republic. As these migrants navigate the integration process, a key aspect of their journey is often their entry into the Czech labor market. The paper aims to identify and analyze selected socio-economic aspects associated with the integration of Ukrainian immigrants, with a specific focus on their Czech language fluency, length of stay in the Czech Republic, and the underlying reasons for their migration. This quantitative research was conducted using a self-designed questionnaire. Data collection took place in the first half of 2023. The sample consisted of 158 Ukrainian immigrants. The results showed statistically significant connections between the subjective assessment of how the respondents communicate in the Czech language with the field in which they work (p < 0.05), the perception of economic status (p < 0.001), the subjective assessment of the difficulty of finding a job (p < 0.001), satisfaction with work (p < 0.005), and intention to change jobs (p < 0.005). Additionally, there are correlations between length of stay and use of original qualification (p < 0.01), reasons for migration and difficulty finding work (p < 0.05), and between subjective evaluation of the difficulty of finding a job in the Czech Republic in relation to coming to the Czech Republic (p < 0.01). The results can be used by counseling centers for foreigners and potential employers to improve Ukrainian employment opportunities in the Czech labor market. AcknowledgmentsThis study is supported by the project GA JU 101/2022/S “Selected aspects of integrating foreigners living in the Czech Republic from the perspective of society and the labor market.”